Erwinia billingiae causes bacterial Canker of Mango (Mangifera indica) in Costa Rica - Vidaurre-Barahona, Daniela (2020)
Introduction. In Costa Rica, bacterial canker of mango has caused economic losses in most of the productive areas since the mid-1980s. The causal agents have been identified only by phenotypic methods such as Erwinia mangifera and E. herbicola. Objective. To confirm, using a molecular and phenotypic approach, the species of the Enterobacteriaceae the cause bacterial canker of mango in Costa Rica. Material and methods. Fruits, branches, and trunks with symptoms were collected in different orchards in the Alajuela province. Bacterial isolation was performed, and pathogenicity was evaluated by inoculating fruits and trunks of the Tommy Atkins variety. The positive isolates for the pathogenic test were re-inoculated, isolated, and identified in order to fulfill Koch’s postulates. The CIBCM-Mg-115 positive isolate that caused symptoms was analyzed by complete biochemical characterization and molecular identification by phylogenetic analyses of 16S rRNA and the atpD, gyrB, infB, and rpoB housekeeping genes. Results. According to the data obtained from the biochemical and molecular analysis, the CIBCM-Mg-115 strain was identified as Erwinia billingiae. Conclusion. E. billingiae corresponds to one of the causal agents of bacterial canker on mango (M. indica) trees in Costa Rica.